Patient involvement in decision-making: A cross-sectional study in a Malaysian primary care clinic - Ambigapathy, R.; Chia, Y.C.; Ng, C.J. (BMJ Publishing Group, 2016)
Objective: Shared decision-making has been advocated as a useful model for patient management. In developing Asian countries such as Malaysia, there is a common belief that patients prefer a passive role in clinical consultation. As such, the objective of this study was to determine Malaysian patients' role preference in decision-making and the associated factors. Design: A cross-sectional study. Setting: Study was conducted at an urban primary care clinic in Malaysia in 2012. Participants: Patients aged 21 years were chosen using systematic random sampling. Methods: Consenting patients answered a self-administered questionnaire, which included demographic data and their preferred and actual role before and after consultation. Doctors were asked to determine patients' role preference. The Control Preference Scale was used to assess patients' role preference. Primary outcome: Prevalence of patients' preferred role in decision-making. Secondary outcomes: (1) Actual role played by the patient in decision-making. (2) Sociodemographic factors associated with patients' preferred role in decision-making. (3) Doctors' perception of patients' involvement in decision-making. Results: The response rate was 95.1% (470/494). Shared decision-making was preferred by 51.9% of patients, followed by passive (26.3%) and active (21.8%) roles in decision-making. Higher household income was significantly associated with autonomous role preference (p=0.018). Doctors' perception did not concur with patients' preferred role. Among patients whom doctors perceived to prefer a passive role, 73.5% preferred an autonomous role (p=0.900, κ=0.006). Conclusions: The majority of patients attending the primary care clinic preferred and played an autonomous role in decision-making. Doctors underestimated patients' preference to play an autonomous role.